A vegetable oil–based biopesticide with ovicidal activity against the two‐spotted spider mite, Tetranychus urticae Koch. Issue 11 (7th October 2020) - Takeda, Naoki; Takata, Ayumi; Arai, Yuka; Sasaya, Kazuhiro; Noyama, Shimpei; Wakisaka, Shigekazu; Ghazy, Noureldin Abuelfadl; Voigt, Dagmar; Suzuki, Takeshi
Abstract: A recently developed biopesticide made of safflower and cottonseed oils has excellent ovicidal activity against the hard‐to‐control spider mite Tetranychus urticae Koch (Acari: Tetranychidae). It has attracted attention as a sustainable treatment for controlling T. urticae because it has low potential for promoting resistance and little effect on the predatory mite Neoseiulus californicus (McGregor) (Acari: Phytoseiidae), which is an important natural enemy of spider mites. Here, we investigated the mechanism of its ovicidal activity against T. urticae . The oil droplets in the oil‐in‐water emulsion of the biopesticide strongly adhered to T. urticae eggs, seeped through the chorion being cut during hatching, and inhibited the embryonic rotational movement necessary for cutting and hatching. No adverse effect was observed on N. californicus eggs even in undiluted biopesticide. We conclude that this biopesticide and N. californicus can be used simultaneously in the integrated management of T. urticae in oily biopesticide‐tolerant plant species.